CHAPLE syndrome uncovers the primary role of complement in a familial form of Waldmann's disease - ÖZEN, AHMET OĞUZHAN (WILEY, 2019)
Primary intestinal lymphangiectasia (PIL) or Waldmann's disease was described in 1961 as an important cause of protein-losing enteropathy (PLE). PIL can be the sole finding in rare individuals or occur as part of a multisystemic genetic syndrome. Although genetic etiologies of many lymphatic dysplasia syndromes associated with PIL have been identified, the pathogenesis of isolated PIL (with no associated syndromic features) remains unknown. Familial cases and occurrence at birth suggest genetic etiologies in certain cases. Recently, CD55 deficiency with hyperactivation of complement, angiopathic thrombosis, and PLE (the CHAPLE syndrome) has been identified as a monogenic form of PIL. Surprisingly, loss of CD55, a key regulator of complement system leads to a predominantly gut condition. Similarly to other complement disorders, namely paroxysmal nocturnal and hemoglobinuria (PNH) and atypical hemolytic uremic syndrome (aHUS), CHAPLE disease involves pathogenic cross-activation of the coagulation system, predisposing individuals to severe thrombosis. The observation that complement system is overly active in CHAPLE disease introduced a novel concept into the management of PLE; anti-complement therapy. While CD55 deficiency constitutes a treatable subgroup in the larger pool of patients with isolated PIL, the etiology remains to be identified in the remaining patients with intact CD55.
Keywords: CD55 deficiency; complement activation; eculizumab; intestinal lymphangiectasia; monogenic IBD; protein-losing enteropathy; PROTEIN-LOSING ENTEROPATHY; HEMOLYTIC-UREMIC SYNDROME; PAROXYSMAL-NOCTURNAL HEMOGLOBINURIA; INTESTINAL LYMPHANGIECTASIA; HENNEKAM-SYNDROME; CONSTRICTIVE PERICARDITIS; EXUDATIVE ENTEROPATHY; MENTAL-RETARDATION; REGULATORY PROTEIN; NEPHROTIC SYNDROME